[OP.7B.02] LONG TERM CHANGES IN LEFT VENTRICULAR MASS: ECHOCARDIOGRAPHIC FINDINGS FROM A GENERAL POPULATION (THE PAMELA STUDY). (September 2017) - Cuspidi, C.; Facchetti, R.; Bombelli, M.; Sala, C.; Tadic, M.; Grassi, G.; Mancia, G.
Abstract : Objective: We sought to perform a comprehensive assessment of long-term changes in left ventricular (LV) mass, focusing on new onset, persistence, regression and severity of LV hypertrophy (LVH), as well as independent demographic and clinical variables related to this dynamic process in a population-based sample. Design and method: A total of 1, 113 participants with measurable echocardiographic parameters at baseline evaluation and at the end of a ten-year follow-up period were included in the present analysis. Cut-points for LVH were derived from current echocardiographic guidelines Results: LVH prevalence significantly increased from 13% to 33%, as a consequence of new onset LVH in 254 and regression in 31 cases, respectively. Severe LVH increased about 1.8 times as compared to baseline and this trend was mainly related to the transition from mild and moderate to severe LVH in subjects with pre-existing cardiac hypertrophy. A number of baseline variables such as age, female gender, office and out-of-office systolic BP, body mass index, ATP 3 metabolic syndrome, and use of antihypertensive drugs were independently correlated either to new-onset and persistent LVH. Conclusions: Long-term LV mass changes in the general population are associated to a marked worsening in cardiovascular risk profile related to increased prevalence and severity of LVH. As BP, metabolic variables and BMI emerged as key correlates of a such dynamic process, our findings suggest that early interventions aimed to modify such risk factors at the community level may have a role in preventing new onset and progression LVH.